Limitation of Notary Obligation in Monitoring the Fairness of Limited Liability Company Service User Transactions - W. I. Airlangga; Sihabudin; L. D. Andreassari (Law and Safety, 2025)
A notary plays a critical role in the Indonesian legal system by ensuring the validity of transactions, especially those involving limited liability companies. As a public official, a notary is entrusted with the responsibility of applying the Principle of Recognizing the Service User, which includes the identification, verification, and monitoring of transactions to prevent illegal activities, such as money laundering. However, regulations like the Minister of Law and Human Rights Regulation No. 9 of 2017 remain vague and do not provide clear guidelines regarding the “fairness of transactions”, resulting in legal uncertainty for notaries. This lack of clear parameters places notaries in a challenging position as they must balance their legal duties, especially when determining what constitutes a suspicious or unfair transaction. This study aims to analyze the limitations of notaries’ obligations in monitoring the fairness of transactions involving PT service users. By using a normative legal research methodology, this research evaluates the legislative and conceptual approaches to building a comprehensive legal framework for notarial duties. The findings highlight that the absence of explicit guidelines causes inconsistent interpretations among notaries, leading to potential conflicts between their obligation to maintain client confidentiality under the Notary Act and their responsibility to report suspicious transactions to the Financial Transaction Reporting and Analysis Center as mandated by the Anti-Money Laundering Law. This study concludes that there is a critical need for clearer regulations and technical guidelines that balance these two competing obligations, thereby enhancing legal certainty and improving the effectiveness of notaries in preventing financial crimes. Strengthening cooperation between notaries and supervisory authorities, as well as providing legal protection for notaries who comply with their reporting obligations, is essential for improving transparency and accountability in the legal profession.